Electron-beam charging of an insulator; Russian Physics Journal; Vol. 17, iss. 1 - Zavadovskaya E. K.; Annenkov Yu. M. Yuriy Mikhailovich; Starodubtsev V. A. Viacheslav Alekseevich; Vakhromeev V. G.; Malofienko G. M. (1974, 1974)
Title screen